Rasmussen's encephalitis: From immune pathogenesis towards targeted-therapy. (October 2020) - Orsini, A.; Foiadelli, T.; Carli, N.; Costagliola, G.; Masini, B.; Bonuccelli, A.; Savasta, S.; Peroni, D.; Consolini, R.; Striano, P.
Highlights: Rasmussen Encephalitis has an autoimmune pathogenesis, but the only definitive treatment is functional hemispherectomy Agents interfering with the immune system are used to treat patients with a slow progression or not eligible for surgery There is no sufficient evidence to support a specific immunosuppressive agent for RE, as the clinical experience is limited Knowledge progress on RE pathogenesis, featuring a T CD8 cell response, has optimized the use of immunosuppressive agents The use of T-targeted treatments represents a promising alternative for the treatment of patients suffering from RE Abstract: Rasmussen encephalitis (RE) is a unilateral hemispheric encephalitis whose main clinical features include refractory focal epilepsy or epilepsia partialis continua, hemiparesis, and progressive cognitive decline. Despite the autoimmune pathogenesis of RE, the only definitive therapeutic option is currently represented by surgery. We review the clinical features, the immune pathogenesis, and the available therapeutic options for RE, with special focus on immunosuppressive agents. The research includes systematic reviews, meta-analyses, observational studies, clinical trials, cases series and reports, until 2020. The use of immunosuppressive agents in RE is supported by the evidence of an autoimmune involvement of the central nervous system in this condition. Although often insufficient to modify the disease course and to achieve symptomatic control, immune therapy can be effective in patients with slow disease progression or in patients in which surgery is not applicable. Moreover, the documentation of T-cell involvement in the pathogenesis of RE, with a specific cytokine pattern, opens a window of opportunity for the use of T-targeted therapies and biologic drugs (i.e. anti-TNFα agents) in the treatment of this disease.